Exploitation and use of non-metal mineral resources of the Tuzla Canton - Nezirović, Senada (Journal for Geography, 2019)
This paper analyzes the spatial distribution of potential non-metallic mineral resources in the area of Tuzla Canton. Available non-metallic mineral resources of the Tuzla Canton are classified into three groups: energy (coal), industrial processing (rock salt, limestone, quartz sand, brick clay and magnesite) and construction materials (gravel and sand). Identification of non-metallic mineral resources of Tuzla Canton described and enumerated all the resources by their importance and use, giving a brief analysis of their economic exploitation. Based on field research, current knowledge, collection of various information and documents, the author tries to point out in the paper the economic importance of non-metallic mineral resources and their participation in the economic development of the Tuzla Canton.